Avaliação Pós-Ocupação da iluminação natural das salas dos setores de aulas teóricas da Universidade Federal do Rio Grande do Norte - Correia, Andreia Gurgel Umbelino (2008)
The objective of this study is to assess the natural light of the classrooms sectors, at Universidade Federal do Rio Grande do Norte. It was applied the Post-Occupation Evaluation technique, by using questionnaires and brightness levels measurements inside the classrooms. In order to check the users satisfaction degree, it was initially done a general approach on the related aspects to natural light: their characteristics, availability, sources, opening systems and evaluating tools. It was also determined the necessary brightness levels for the activities development in the classroom and the Post-Occupation Evaluation technique used in the search analyses. Then, it was made the UFRN Campus` characterization; the models` definition which formed the data collection basis; the detailing of the procedures used in the research, the processing description and the data analysis. Subsequently, the results that clarify the issues raised were shown through quantitative and / or qualitative data analyses. This research notes a high level of satisfaction by the users, despite some problems such as the reflections occurrence on the board, the lack of uniformity and, occasionally, the brightness low levels